Ecotourism. - Fennell, David A., 1963- (Routledge, 2020)
"The new edition focuses on economic, social and ecological inconsistencies that continue to plague ecotourism in theory and practice, and examines the sector in reference to other related forms of tourism, impacts, conservation, sustainability, education and interpretation, policy and governance, and the ethical imperative of ecotourism. An essential reference for those interested in ecotourism, the book is accessible to students, but retains the depth required for use by researchers and practitioners in the field. It book will be of interest to students across a range of disciplines including geography, economics, business, ethics, biology, and environmental studies"--